Acetylcholine-Based Entropy in Response Selection: A Model of How Striatal Interneurons Modulate Exploration, Exploitation, and Response Variability in Decision-Making - Stocco, Andrea (Frontiers in Neuroscience, 2012)
The basal ganglia play a fundamental role in decision making. Their contribution is typically modeled within a reinforcement learning framework, with the basal ganglia learning to select the options associated with highest value and their dopamine inputs conveying performance feedback. This basic framework, however, does not account for the role of cholinergic interneurons in the striatum, and does not easily explain certain dynamic aspects of decision-making and skill acquisition like the generation of exploratory actions. This paper describes BABE (Basal ganglia Acetylcholine-Based Entropy), a model of the acetylcholine system in the striatum that provides a unified explanation for these phenomena. According to this model, cholinergic interneurons in the striatum control the level of variability in behavior by modulating the number of possible responses that are considered by the basal ganglia, as well as the level of competition between them. This mechanism provides a natural way to account for the role of basal ganglia in generating behavioral variability during the acquisition of certain cognitive skills, as well as for modulating exploration and exploitation in decision making. Compared to a typical reinforcement learning model, BABE showed a greater modulation of response variability in the face of changes in the reward contingencies, allowing for faster learning (and re-learning) of option values. Finally, the paper discusses the possible applications of the model to other domains.